2009
DOI: 10.1248/yakushi.129.593
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Potential of Spironolactone in Diabetes Induced Hyperalgesia in Mice

Abstract: The present study was designed to investigate the ameliorative potential of spironolactone against diabetic hyperalgesia in mice. Tail ‰ick latency, an index of hyperalgesia, was assessed by analgesiometer. Serum nitrite levels, an index of nitric oxide, were analyzed by Griess reaction. Mice were rendered diabetic with streptozotocin (200 mg kg -1 i.p) and kept for 30 days for development of diabetic pain. Thereafter, spleen homogenate supernatant (SHS) was prepared from the mouse spleen and administered in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…35 A study from our laboratory has also reported the anti-hyperalgesic effect of spironolactone in diabetic neuropathic pain. 28 Spironolactone has also been shown to attenuate acetic acid-induced inflammatory visceral pain in mice. 36 The repeated administration (not single dosing) of spirapril and losartan has been shown to elicit anti-nociceptive actions, suggesting the nociceptive role of the brain endogenous AngII.…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…35 A study from our laboratory has also reported the anti-hyperalgesic effect of spironolactone in diabetic neuropathic pain. 28 Spironolactone has also been shown to attenuate acetic acid-induced inflammatory visceral pain in mice. 36 The repeated administration (not single dosing) of spirapril and losartan has been shown to elicit anti-nociceptive actions, suggesting the nociceptive role of the brain endogenous AngII.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…both pain attenuation and increased pain sensitivity with RAS blockers. [28][29][30] However, it is difficult to explain the exact mechanism, as there are no direct studies to understand the duality of angiotensin neuropeptides in pain. The evidence regarding the analgesic role of RAS blockers has mainly come from preclinical and clinical studies in which inflammation is a predominant feature (e.g.…”
Section: Possible Hypothesis For Dual Actions Of the Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…High glucose levels may induce glycation of various structural and functional proteins including plasma proteins and collagen [6]. The non-enzymatic modification of plasma proteins such as albumin, fibrinogen and globulins may be produce various deleterious effects including alteration in drug binding in the plasma, platelet activation, generation of oxygen free radicals, impaired fibrinolysis and impairment in immune system regulation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3 Interestingly, spironolactone accentuates the antinociceptive potential of steroids such as dexamethasone. 4 This synergistic effect of spironolactone is mediated by its antagonistic effect on mineralocorticoid receptors.…”
Section: To the Editormentioning
confidence: 99%